2007
DOI: 10.1002/chem.200700267
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X‐ray Diffraction and Computational Study of the Crystal Packing of Polycyclic Hydrocarbons Featuring Aromatic and Perfluoroaromatic Rings Condensed in the Same Molecule: 1,2,3,4‐Tetrafluoronaphthalene, ‐anthracene and ‐phenanthrene

Abstract: We have synthesised some planar polycyclic compounds, in which unsubstituted aromatic rings are condensed with perfluorinated aromatic rings, and have carried out a combined X-ray diffraction and computational study to analyse their self-recognition behaviour in crystalline phases. We compare our results with the parent hydrocarbons and with other compounds that have a variable degree of fluorination. Whereas the molecular planes in crystals of hydrocarbons with mono- or difluorinated aromatic rings or of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 23 publications
7
51
1
2
Order By: Relevance
“…38 • rotation around the molecular C 2 axis. Our results essentially agree with those of Gavezzotti et al 33 although the better crystal quality allowed all atoms to be refined in anisotropic approximation and gave a much improved R-factor (3.1% vs 11.6%). The relative occupancies of the two orientations were refined, converging at 54.2(7) and 45.8(7)%.…”
Section: Analysis X-ray Diffractionsupporting
confidence: 90%
“…38 • rotation around the molecular C 2 axis. Our results essentially agree with those of Gavezzotti et al 33 although the better crystal quality allowed all atoms to be refined in anisotropic approximation and gave a much improved R-factor (3.1% vs 11.6%). The relative occupancies of the two orientations were refined, converging at 54.2(7) and 45.8(7)%.…”
Section: Analysis X-ray Diffractionsupporting
confidence: 90%
“…5). This supramolecular organization was also found in others three-fused rings related compounds [43]. In this interaction the molecules are related by translational symmetry along the crystallographic a axis and the anthracene rings are parallel with the corresponding centroids accordingly displaced.…”
Section: Molecular and Supramolecular Structuresupporting
confidence: 78%
“…It was proposed that one of the hypothetical (computed) high pressure forms of benzene adopts the same tetragonal packing as fluorobenzene and hence C-H···F-C interactions behave similar to C-H···H interactions and have the same structure-directing ability. This conclusion was further supported in the crystal packing analysis of 1,2,3,4-tetrafluoronaphthalene, -anthracene, and -phenanthrene by Gavezzotti et al [69]. It was observed that the C-H···F-C interactions does not provide any significant stabilization to the crystal packing.…”
Section: Why Fluorine Is So Special?mentioning
confidence: 58%